BIOCLIMATIC ARCHITECTURE APPROACH TO ENERGY EFFICIENT SCHOOL BUILDING CONCEPTS - Megawati, Lia Amelia; Akromusyuhada, Akhmad (Universitas Sebelas Maret Surakarta, 2019)
Bioclimatic architecture is an integrated concept in building design where the structure, space and building construction systems can guarantee comfortable conditions for the occupants. This concept was developed in the building of SMU Al Wahid Kabupaten Tasikmalaya which is physically a school building far from comfortable. The form of school buildings does not support the implementation of good quality teaching and learning activities, so that redesign is needed to support the comfort of school building users. Contoured area locations, beautiful environment and adequate air temperature are sufficient to support the application of bioclimatic architectural concepts. To obtain accurate primary data, the Post Occupancy Evaluation method is used. This study focused on building users, needs and provided insight into the consequences of existing designs. The evaluation results will be used as planning criteria in the program and subsequent design. Bioclimatic architecture is implemented in the hope of increasing the comfort of users of school facilities so that the process of teaching and learning can run optimally.